ARTIFICIAL INTELLIGENCE USED FOR DEVELOPMENT OF BUSINESS MANAGEMENT - BORCOȘI CORINA ANA (Analele Universităţii Constantin Brâncuşi din Târgu Jiu : Seria Economie)
The development of business management will depend in the future on the approach, the way of accessing but also the way of using data and technologies that are in continuous evolution, development. The faster we understand how to use the news from all fields, the faster we will connect to the current world, which will bring us development, evolution, prosperity in the business world, but also in our personal lives. Since the volume of data around the world is of the order of thousands of billions of gigabits, artificial intelligence (AI) was created, which represents an essential technology of the future, that imitates human functions: it is creative, has reasoning, has the ability to learn continuously. Systems that have AI can adapt their behavior depending on the results obtained from previous actions, and can also function autonomously. Technologies that incorporate AI have existed for over 50 years, but great progress in the use of AI has been achieved in recent years, due to the desire, the need to use the large volumes of data that exist worldwide. AI can be used in all fields. In this paper we will refer to the utility of AI to develop businesses, to improve business management. We will study the specialized scientific literature to emphasize the contribution made by AI to the development of business management. We will also present the future research directions, inspired by the themes presented in this paper.